An IoT-based architecture for human resource management in construction sites using software defined networking (SDN) and game theory - Xuejie Niu (Egyptian Informatics Journal)
Construction sites are notoriously hazardous. This paper explores how the Internet of Things (IoT) can improve worker safety and resource management in these complex environments. Traditional monitoring systems struggle with managing diverse sensor data and ensuring scalability on large construction projects. This research proposes a novel architecture that leverages Software-Defined Networking (SDN) to manage an IoT network of environmental, biometric, and surveillance sensors. This centralized control enables efficient topology control and improved network performance. Furthermore, a game-theoretic approach is employed to optimize resource allocation and routing decisions, minimizing interference and maximizing network throughput. The proposed approach achieves significant enhancements in key network metrics: delay is reduced by 59.49%, energy consumption drops by 18.31%, and packet delivery rate increases by 7.70%. This research demonstrates the potential of SDN-based IoT architectures to revolutionize safety and resource management in construction, paving the way for future advancements in on-site worker well-being and project efficiency.